2012
DOI: 10.1016/j.addbeh.2011.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for substance use among people with mental disorders

Abstract: It may be important to tailor interventions for co-existing mental disorders and substance use by substance type and type of mental disorder. For example, interventions might be improved by including alternative coping strategies to tobacco and/or alcohol use, by addressing the social role of alcohol and by helping people with mental disorders using cannabis to gain pleasure from their lives in other ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
3
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 42 publications
(61 reference statements)
3
66
3
8
Order By: Relevance
“…Students with poor mental health, relative to peers with strong mental health, tend to endorse stronger motivations for drinking (e.g., Cooper et al, 1995;Thornton et al, 2012). Specifi cally, evidence supports that students with poor mental health usually drink to reduce or regulate negative internal (coping motives) or external (conformity motives) states (McNally et al, 2003;O'Hare and Shen, 2012;Windle and Windle, 2012).…”
Section: Mental Health and Drinking Motives On Alcohol Outcomesmentioning
confidence: 99%
“…Students with poor mental health, relative to peers with strong mental health, tend to endorse stronger motivations for drinking (e.g., Cooper et al, 1995;Thornton et al, 2012). Specifi cally, evidence supports that students with poor mental health usually drink to reduce or regulate negative internal (coping motives) or external (conformity motives) states (McNally et al, 2003;O'Hare and Shen, 2012;Windle and Windle, 2012).…”
Section: Mental Health and Drinking Motives On Alcohol Outcomesmentioning
confidence: 99%
“…In contrast to individuals with AUD and AD, those with MD may be more socially isolated and less motivated to smoke in public settings, such as restaurants and bars. For example, Thornton et al (2012) found that only 9% of those with depression reported social motives for smoking (Thornton et al, 2012). We also did not find significant interactions with psychiatric disorders when examining cigarette consumption, among those who continued to use tobacco.…”
Section: Discussionmentioning
confidence: 59%
“…Essa estratégia parece motivar o uso de cannabis em pacientes com vulnerabilidade a ansiedade (Johnson el al., 2010) mas é uma motivação secundária em pacientes com psicose ou depressão (Thornton et al, 2012), que relatam buscar na droga um aumento do prazer. Não há evidências de aumento no valor hedônico de estímulo prazerosos, sendo necessário mais estudos ligados a percepção desses em usuários de cannabis.…”
Section: Uso De Cannabis E Psicopatologiaunclassified